Intraprocedural activated clotting time and heparin dosage in pulsed field ablation of paroxysmal atrial fibrillation - Chengming Ma; Xianjie Xiao; Qian Chen; Wenwen Li; Zhongzhen Wang; Shiyu Dai; Yuanjun Sun; Yunlong Xia; Lianjun Gao; Xiaomeng Yin (Frontiers in Cardiovascular Medicine)
AimsWhether the intraprocedural anticoagulation regimen and activated clotting time (ACT) in pulsed field ablation (PFA) for atrial fibrillation (AF) are the same as those for radiofrequency catheter ablation (RFCA) is currently unknown.Methods and resultsOur retrospective study included 51 paroxysmal AF patients who underwent PFA (PFA group) and were matched with paroxysmal AF patients who underwent RFCA. Nearest-neighbor propensity score matching was performed at a 1:1 ratio (no tolerance to anticoagulant regimens and a tolerance of 0.02 on the CHA2DS2-VASc score, left atrial diameter, and left ventricular ejection fraction). Compared with the RFCA group, the PFA group had a significantly shorter procedure time but a longer fluoroscopy time. In both groups, an initial heparin dose of 110 U/kg was given. The 30-min ACT in the PFA group (240 ± 95.5 s) was shorter than that in the RFCA group (294.4 ± 82.3 s, P = 0.003). The 60-, 90-, and 120-min ACTs were significantly longer in the PFA group. The percentage of 30 min-ACTs in the therapeutic range in the RFCA group (33.3%) was greater than that in the PFA group (15.7%, P = 0.038). The time to achieve the target ACT was longer in the PFA group. There were no differences in the incidence of periprocedural thromboembolism or bleeding events between the two groups.ConclusionsCompared with RFCA, PFA was associated with longer intraprocedural ACTs, shorter initial ACTs, fewer initial ACTs in the therapeutic range, and longer times to achieve the target ACT.